Pendidikan Kewarganegaraan dan Pembentukan Karakter: Membentuk Individu yang Bertanggung Jawab dan Peduli - Yudha, Willy Fadhilah Wira; Hudi, Ilham; Marisa, Vania; Farliando, Ridho Arya; Putri, Yolanda Ardila; Avicenna, Achyar Zein; Admi, Nurhayati Marjuni (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Citizenship education is an important component in character formation that can improve the moral quality of the Indonesian nation. Citizenship education can be an effort to create character or   morals   based   on   Pancasila regarding   the understanding, values , and behavior of the nation's generation. In character formation, citizenship education is the main effort to improve skills in terms of critical thinking, collaborative communication skills, and good decision-making skills. Citizenship education focuses onl  forming a quality young generationlby optimizing the potential in each individual which is reflected in awareness, understanding, and behavior. With Citizenship Education, it is hopedl  that it can be an effort to strengthen the identity and quality of the nation by creating individuals whol   are not only intellectually intelligent but  also have  strong,  responsive,  critical,  creative,  responsible  character  and  can contribute positively to societyl  andl  the nation.